VD_FINDINFO Jug / 2012 / 72 vom 29. September 2011 - VD Tribunal cantonal (2011)
CONSTATATION DES FAITS, ÉTAT DE FAIT, PEINE PÉCUNIAIRE | 34 al. 2 CP, 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH)